Пошаговое объяснение:
3 : 8 * у - 4 = -15 + у : 8
3/8у - 4 = -15 + 1/8у
3/8у - 1/8у = -15 + 4
2/8у = -11
у = -11 : 2/8
у = -11 * 8/2
у = -88/2
у = -44
-3(3х - 5) = -6 - 7(х - 5)
-9х + 15 = -6 - 7х + 35
-9х + 7х = -6 + 35 - 15
-2х = 14
х = 14 : (-2)
х = -7
Пошаговое объяснение:
3 : 8 * у - 4 = -15 + у : 8
3/8у - 4 = -15 + 1/8у
3/8у - 1/8у = -15 + 4
2/8у = -11
у = -11 : 2/8
у = -11 * 8/2
у = -88/2
у = -44
-3(3х - 5) = -6 - 7(х - 5)
-9х + 15 = -6 - 7х + 35
-9х + 7х = -6 + 35 - 15
-2х = 14
х = 14 : (-2)
х = -7